The relation between temporomandibular disorders, mood status and serotonin transporter gene polymorphism. Study in Syrian population. (Mustansiria Dental Journal, 2018)
The purpose of this study was to evaluate the relationship betweentemporomandibular disorders, mood status and serotonin transporter (5-HTT) genepolymorphisms in Syrian population. Twenty patients with temporomandibular jointdisorder (TMD), and 36 healthy control subjects were examined. The sample consistsof 23 males, and 33 females aged between (19-30 years old), visited the department offixed prosthodontic of the faculty of dentistry, Damascus University. This studyshows that S/L allele of 5-HTTLPR was the most frequently observed allele in TMDpatients; whereas statistical analysis did not show significant difference betweenpatient and control groups by neither genotype distribution analysis nor allelefrequency analysis. S\S allele analysis showed a relation between it and mood status.Although the study did not show significant relation between TMD and serotonintransporter polymorphism gene, but according to the importance of serotonintransporter polymorphism gene and its relation to psychological factors we suggestother studies which focus on the relation between the genetics, psychology and TMD.